Plasma vascular adhesion protein-1 levels correlate positively with frailty severity in older adults. Issue 30 (24th July 2020) - Huang, Hsien-Liang; Chang, Chin-Hao; Chen, Chin-Ying; Peng, Jen-Kuei; Wang, Yu-Ting; Chen, Ching-Yu; Hsu, Chih-Cheng; Lee, Chung-Sheng; Tsai, Jaw-Shiun
Abstract : Abstract: Geriatric frailty is associated with increased mortality and links to increased inflammatory activity. Vascular adhesion protein-1 (VAP-1) is important in inflammatory process. This study investigates the relationship between plasma VAP-1 level and frailty in older adults. The cross-sectional study recruited community dwelling older adults from a hospital-based comprehensive geriatric assessment program. The demographic data, Fried Frailty Index, metabolic and inflammatory parameters were assessed. A total of 151 participants (76 women, 50.3%) were included in the analysis, and the age (mean ±  standard deviation) was 77.1 ± 6.1 years. The mean plasma VAP-1 level (ng/mL) was significantly different ( P  = .029) among different frailty groups (346.3 ± 86.5 in the robust older adults, 371.6 ± 107.9 in the pre-frail older adults, and 416.6 ± 141.1 in the frail older adults). Multivariate ordered logistic regression analysis also demonstrated that plasma VAP-1 levels were positively associated with frailty severity ( P  = .039). Analysis of the frailty components with plasma VAP-1 levels showed that the elderly who had "exhaustion" ( P  = .016) or "weakness" ( P  = .025) tended to have higher plasma VAP-1 levels. The data support that VAP-1 might represent a potential plasma biomarker of frailty.